Elaboración de un plan de mantenimiento para la Empresa Metalmecánica Indumetalsa S.A.S. (2022)
This document presents as its main objective the development of a maintenance plan for the assets of the metalworking company INDUMETALSA SAS, which to date does not have an established plan and the machines are intervened only when they are disabled for their operation, which entails having cost overruns due to downtime for both the machine and its operator, in addition to high repair costs when carrying out purely corrective maintenance, which implies low reliability and reduced production, since these repairs have interrupted activities for up to more of 5 days generating considerable losses. This company is dedicated to industrial maintenance, the manufacture of extrusion molds and special machining for which it is essential to have the availability of the machines since these maintenance and manufacturing activities must be carried out and delivered in certain times. Therefore, this document deals with showing in detail an analysis of the company's assets that through visits to the facilities proceeded to give a diagnosis of the machines, as well as characterize each one of them by making an analysis of the important parts. that affect the operation of the same, later an evaluation was carried out between the maintenance strategies TPM, RCM and AMEF to determine which of them adapts to the needs and the assets of the company with this evaluation it was concluded that the analysis of mode and Failure effect is the appropriate strategy for the company since the structure of the FMEA will allow concentrating the information regarding the modes, effects, causes of failures and establishing maintenance activities among other components that comprise the plan. Finally, provide a solution to the problem of unproductiveness and cost overruns for repairs by developing this maintenance plan that will increase the reliability and availability of the assets of INDUMETALSA S.A.S.